Seroprevalence of Schistosoma mansoni in Puerto Ricans with Inflammatory Bowel Disease - Torres, Esther A.; Acosta, Héctor; Cruz, Marcia; Weinstock, Joel; Hillyer, George V. (Puerto Rico Health Sciences Journal, 2013)
See manuscript